Enhancing Robot Programming through Digital Twin and Augmented Reality - Yigitbas, Enes; Engels, Gregor (56th Hawaii International Conference on System Science (HICSS 2023))

Towards Enhanced Guiding Mechanisms in VR Training through Process Mining - Yigitbas, Enes; Krois, Sebastian; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 7th International Conference on Human Computer Interaction Theory and Applications (HUCAPP'23))

Cortical thickness and neurocognitive performance in former high‐level female soccer and non‐contact sport athletes - Haase, Franziska Katharina; Prien, Annika; Douw, Linda; Feddermann‐Demont, Nina; Junge, Astrid; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

New Quick And Easy Publication - Will be edited by LibreCat team - Matthias Philipper (Quick And Easy Journal Title)

Tailored Frequency Conversion Makes Infrared Light Visible for Streak Cameras - Lüders, Carolin; Gil-Lopez, Jano; Allgaier, Markus; Brecht, Benjamin; Aßmann, Marc; Silberhorn, Christine; Bayer, Manfred (Physical Review Applied)
Keywords: General Physics and Astronomy

A Unifying Approach to Efficient (Near-)Gathering of Disoriented Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Proceedings of the 26th International Conference on Principles of Distributed Systems (OPODIS))

Learning a model is paramount for sample efficiency in reinforcement learning control of PDEs - Werner, Stefan; Peitz, Sebastian (arXiv:2302.07160)
The goal of this paper is to make a strong point for the usage of dynamical models when using reinforcement learning (RL) for feedback control of dynamical systems governed by partial differential equations (PDEs). To breach the gap between the immense promises we see in RL and the applicability in complex engineering systems, the main challenges are the massive requirements in terms of the training data, as well as the lack of performance guarantees. We present a solution for the first issue using a data-driven surrogate model in the form of a convolutional LSTM with actuation. We demonstrate that learning an actuated model in parallel to training the RL agent significantly reduces the total amount of required data sampled from the real system. Furthermore, we show that iteratively updating the model is of major importance to avoid biases in the RL training. Detailed ablation studies reveal the most important ingredients of the modeling process. We use the chaotic Kuramoto-Sivashinsky equation do demonstarte our findings.

Circularly Polarized Lasing from a Microcavity Filled with Achiral Single‐Crystalline Microribbons - Liang, Qian; Ma, Xuekai; Long, Teng; Yao, Jiannian; Liao, Qing; Fu, Hongbing (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Improving students’ attitudes towards peers with special needs: Results from an intervention study. Symposium "Chances and challenges in diverse classrooms" (Sepideh Hassani & Marwin Felix Loeper). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Prerequisites for primary school teachers’ practices in the inclusive classroom. Symposium "Applying the Theory of Planned Behavior in Inclusive Education« (Olli-Pekka Malinen). 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank